THE INSTITUTIONALIZATION OF GLOBAL STRATEGIES FOR THE TRANSFORMATION OF SOCIETY AND EDUCATION IN THE CONTEXT OF CRITICAL THEORY - Viktor V. Zinchenko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose. Critical social philosophy of education strives to provide a radical critique of existing models of education in the so-called Western models of democracy, creating progressive alternative models. In this context, the proposed integrative metatheory, which is based on classical and modern sources, concepts, aims for a comprehensive understanding and reconstruction of the phenomenon of education. One of the main tasks in the sphere of education’s democratization today, therefore, is to bring to education the results of restructuring and democratization of the society, to reflect changes in conditions of life and thinking, experience and transformation of subjectivity in the context of the technological revolution and globalization. Methodology. The critical social theory, which developed in the framework of contemporary neo-Marxism, indicates the need for a thorough analysis of society, however, unlike other theoretical concepts and research programs in order to analyze not a fixation and a statement of the existing social givens. On the contrary, critical analysis of society involves the identification of existing antagonistic, alienating factors that distort public communication.The subject of social analysis is the whole sphere of human and non-human nature, which interacts a person depend on it, the whole system of relations between society and nature, society and man, which is covered by the historical practice of conscious – "praxis". The representative of "pure science" isn't the learning, research subject. He is a public a person, which is the totality of all social definitions included in society and its constituent individuals. For such a "total subject" Object of interest is not something external; on the contrary, the latter appears as a product of his own activity. The scientific novelty examines trends in educational institutions and models of globalizing society in the context of our particular relationship of education and society, man and the state, and processes. The research and systematic analysis of neoliberal reforms at the level of society in general and education in particular are conducted. It examines substantive, structural and functional characteristics of the concept of «critical social philosophy of education» in the context of institutional tendencies of social life, as well as forms and possibilities of its methodological application. It consider a model of «critical social philosophy of education», as embodied in the programs of social development and learning, which are primarily designed to teach people how to lead an independent and original research themselves, society and knowledge systems. However, it is proved that the models and programs should not be cut off from any individual and the collective system of moral and social values, theoretical and applied training, nor from further use of the acquired values, norms and skills in everyday life, science, or in production, sphere of all social institutions. Conclusions. Critical philosophical, educational, pedagogical-psychological surprisingly theory, its models and concepts seek to redefine public and private and the public mind. Based on these grounds, in the future, it allows philosophy of education to develop a more inclusive philosophical vision of education, to apply directly to the problems of democratization and changes in social relations in the direction of equality and social justice in the field of education. The point of view of socio-philosophical and philosophical-еducational, pedagogical-psychological, normative understanding and social critics also requires the use of active efforts in the reconstruuction of education and society, the social vision of what education and human life can be and what their specific limitations in existing societies.